UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI PERMAINAN KECIL DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Muhamad Anwarudin, - (2020)
The purpose of this study was to find out if small games can increase students' learning motivation in physical education learning. The research method used in this research is Class Action Research (PTK). The research design used in this research is john elliott ptk design model. Participants involved in this study were members of the Cimahi Two City Futsal Club as many as 30 people. The data of the research was collected through motivational questionnaires, observation sheets, and field records. The data collected will then be analyzed using SPSS program through descriptive statistics, Normality Test with Kolmogorov-Smirnov Test approach, and Improvement Test using Paired Sample Test approach. The results showed a significant increase in Paired Sample Test results in each cycle and every action given. So it can be concluded that small games given to students before doing physical education learning can increase the motivation of students' learning.